Social Identification and Positioning in Academic Discourse: An English-Polish Comparative Study - Lehman, Iga Maria (Academic Journal of Modern Philology, 2015)
This article sets out to present the critical role of positioning theory and social identification theory in the discoursal analysis of authorial presence in academic texts by focusing on the dynamic nature of writer identity. Drawing on Harré’s, Fairclough’s and Hall’s work, and my own focus on the relationship between students’ identities and their experience of academic writing, I claim that discoursal identity often establishes itself in relation to difference and that it refers to the various “selves” which writers employ in the act of writing, which locates identity in socio-cultural and institutionally defined subject positions. An empirical case is then presented. It consists of a description of my own semi-ethnographic study1 on the co-construction of authorial identity in student writing in both English and Polish, focusing on the findings of the macro-level analysis of a text corpus. The findings of the study support my other claim thatauthorial identity is a dynamic concept which cannot be determined entirely by socio-cultural or institutional factors, but is unique for each writer and can be negotiated and changed.